On the Stability of Resistively Variable Capacitors Using General Impedance Converters - Muhammad Taher Abuelma'atti; Muhammad Haroon Khan (Active and Passive Electronic Components)
The stability of three recently proposed circuits for realizing resistively variable capacitors is studied. It is shown that the circuits may oscillate for practical values of active and passive components. Simulation and experimental results are included.